Analisis Perbaikan Kualitas Jasa Layanan Parkir Sepeda Motor Kampus UAJ Semanggi - Trifenaus Prabu Hidayat; Andre Sugioko; Jordan Adrian (Universitas Bunda Mulia, 2017)
PT X Indonesia is Facility services company. The scope one of service from this company is managing parking area. Consumers of these companies come from various circles, such as Atma Jaya Catholic University of Indonesia. The management intended to give comfort to motorcycle users. But it is undeniable that the users often feel the deficiency in service provided by the company. Therefore, there needs to analyze important analyze the attributes that have not met expectations of the user. The results of the analysis will be used to provide a solution for PT X Indonesia. in this paper, will use the grey relation analysis method. Grey relation analysis is a weighting method to determine the performance attributes. This method uses a questionnaire to obtain answers from the user. Based on the method selected five attributes that represent the security in the parking area, comfort a canopy (roof guards), and the services at the counter. This paper uses three approach analysis, such as cause analysis, system simulation, and value stream mapping service. The results of this research is an increase in the number of officers watching, installation, CCTV images, the use of a new payment system that is tapping card, use canopy to pedestrian path on the area in the parking lot and an increase in the number of the counter.Keywords: PT. X Indonesia, Parking Service, Grey Relation Analysis